Corporate Governance, Green Investment, and Carbon Emission Disclosure Moderated by Environmental Reputation - Kusumajaya, I Made Dwi; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 35 No 7 (2025), 2025)
This study explores the voluntary disclosure of carbon emissions in sustainability reports. It examines the influence of good corporate governance and green investment on this disclosure, with environmental reputation serving as a moderating factor. The analysis was conducted on 131 energy companies listed on the Indonesia Stock Exchange from 2018 to 2022 using moderated regression analysis with the subgroup method. Interpretations of the research findings through the lens of stakeholder theory and the contingency approach reveal that while good corporate governance and its interaction with environmental reputation do not significantly affect carbon emission disclosure, green investment and its interaction with environmental reputation significantly impact the disclosure levels. Keywords: Carbon Emission Disclosure; Good Corporate Governance; Green Investment; Environmental Reputation